Reviewing the Maintenance of Acehnese Language from the Language Policy and Planning Perspectives - Rahmatillah, Refanja; Syahputri, Veni Nella; Rahma, Endah Anisa; Fajrita, Rizki (Universitas Teuku Umar, 2021)
For over the last decade, the number of Acehnese speakers has continuously declined. The obstruction of Acehnese transfer from one generation to the next generation is believed to contribute to this condition. This paper addresses the role of language policy and planning to overcome the mentioned problem. The situation of Acehnese use and the studies related to this topic are reviewed to conclude the suggestions for the improvement of Acehnese language policy and planning. The results of the review indicate that the Acehnese language policy and planning is not well prepared, specifically related to corpus planning which affects Acehnese teaching in school. In addition, the local government does not optimally support the efforts of using Acehnese in public.